Resistência de uma população de Haemonchus contortus ao monepantel no Espírito Santo, Brasil - Viana, Marcus Vinicius Gonçalves (2021)
The objective of this work was to evaluate the efficacy of treatment with anthelmintic (monepantel) on the populations of gastrointestinal nematodes in sheep, and the study is divided into two studies. In the first, the history of the active ingredients used in the herd of the farm was carried out during the last five years and three efficacy tests were performed to evaluate the main drugs used over the years. It was verified that monepantel is being used in the property since 2014, presenting efficacies of 96, 64 and 1%, respectively in the years 2015, 2017 and 2019. In the second stage, 14 lambs, males and females with a mean age of 130 days, allocated in two experimental groups were selected: control and treated. After the OPG analyses of the fecal samples, the animals were divided into two groups, the treated group was medicated with 1mL/10 kg of monepantel, while the control group did not receive any treatment with anthelmintic. After 7 days of treatment, the animals were euthanized for recovery of parasite in the gastrointestinal tract. The material was analyzed, performing the counting and identification of the parasitos. The calculation for efficacy evaluation showed a reduction of 61%, demonstrating anthelmintic resistance of Haemonchus contortus and values suggestive of resistance of Oesophagostomum columbianum to monepantel.